Relational Database Principles Consideration for SQL Programming - Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2023)
In practice, SQL programmers often encounter queries which are hard to formulate using SQL statements. Many of them do not know if the queries are too hard beyond their capabilities, or they are the limitations of the language. Many of these programmers only know that SQL statements work on database tables and are not aware of relational database and the relational complete language principle. This paper presents the common problems that SQL programmers encounter and refers to the relevant relational database principles as solutions.
Keywords: Delete Problems; Insert Problems; Query Problems; Relational Database; SQL; Surrogate key